Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/ijfs.14550
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and evaluation of physicochemical properties of probiotic edible film based on pectin–alginate–casein composite

Abstract: Summary The objective of this study was to develop a casein‐based edible film for the entrapment of probiotic Enterococcus faecium Rp1. Casein, pectin, sodium alginate and glycerol were used to prepare the film. In this study, the physicochemical and morphological properties of casein‐based edible film and its impact on the stability of probiotic were evaluated. Surface morphology and properties of the film were tested using a scanning electron microscope, fluorescence microscopy, Raman spectroscopy, Fourier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…This may be due to the absence of flaxseed gum in this sample, as the addition of flaxseed gum during preparation of the film significantly improved (p > 0.05) the thickness of the resulting films. These results were in concordance with a study by Namratha et al [36], which reported that films are more stable and more complex with the addition of pectin. The various authors reported the non-significant effect of different concentration of glycerol on the thickness of the film [37].…”
Section: Thicknesssupporting
confidence: 93%
“…This may be due to the absence of flaxseed gum in this sample, as the addition of flaxseed gum during preparation of the film significantly improved (p > 0.05) the thickness of the resulting films. These results were in concordance with a study by Namratha et al [36], which reported that films are more stable and more complex with the addition of pectin. The various authors reported the non-significant effect of different concentration of glycerol on the thickness of the film [37].…”
Section: Thicknesssupporting
confidence: 93%
“…Classification of the food packaging materials according to activity and composition. [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128].…”
Section: Drug Delivery Systems As Packaging Materialsmentioning
confidence: 99%
“…An extensive review in the field was published by Pavli et al in 2018 and it concluded that most of the biopolymers can host probiotics while the derived food packaging could be used in several applications such as yogurt, cheese, juice, and chocolate protection [120]. For instance, Namratha et al [121] developed some composite films based on pectin, alginate, and casein and loaded them with a probiotic, namely Enterococcus faecium Rp1. Glycerol was used as a plasticizer and the quaternary systems exhibited significant improvements in the antimicrobial and antioxidant performances along with enhanced structural, optical, and thermal properties while the viability of the probiotics was maintained up to 30 days at 4 • C.…”
Section: Probiotic Loaded Food Packagingmentioning
confidence: 99%
“…In this arena, many biopolymer‐based EC is showing wide usage, among which pectin is a potential candidate with documented success in protecting fresh and fresh‐cut fruits and vegetables (Radi et al ., 2018; Phinainitisatra & Harnkarnsujarit, 2021). In this arena, pectin‐based films and coatings have proven to be effective packaging materials and carriers of functional components (Namratha et al ., 2020; Otálora González et al ., 2020). Pectin‐based EC formulated as emulsions and nanoemulsions (NEs) is currently being applied as carriers of various compounds enhancing their functionality by conferring antimicrobial and antioxidant properties to them (Hasan et al ., 2020; Rehman et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%